Phenotypic variance explained by local ancestry in admixed African Americans - Shriner, Daniel; Bentley, Amy R.; Doumatey, Ayo P.; Chen, Guanjie; Zhou, Jie; Adeyemo, Adebowale; Rotimi, Charles N. (Frontiers in Genetics, 2015)
We surveyed 26 quantitative traits and disease outcomes to understand the proportion of phenotypic variance explained by local ancestry in admixed African Americans. After inferring local ancestry as the number of African-ancestry chromosomes at hundreds of thousands of genotyped loci across all autosomes, we used a linear mixed effects model to estimate the variance explained by local ancestry in two large independent samples of unrelated African Americans. We found that local ancestry at major and polygenic effect genes can explain up to 20% and 8% of phenotypic variance, respectively. These findings provide evidence that most but not all additive genetic variance is explained by genetic markers undifferentiated by ancestry. These results also inform the proportion of health disparities due to genetic risk factors and the magnitude of error in association studies not controlling for local ancestry.